2005
DOI: 10.1111/j.1600-0714.2005.00364.x
|View full text |Cite
|
Sign up to set email alerts
|

Gene–environment interaction involved in oral carcinogenesis: molecular epidemiological study for metabolic and DNA repair gene polymorphisms

Abstract: CYP2E1, XPA and ERCC1 polymorphisms may affect the risk of OSCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
61
1
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(68 citation statements)
references
References 35 publications
4
61
1
2
Order By: Relevance
“…Among the 28 eligible articles, 18 articles (Bai et al 2007;Blankenburg et al 2005;Festa et al 2005;Hansen et al 2007;Hirata et al 2007;Hu et al 2005;Huang et al 2006;Kietthubthew et al 2006;Lee et al 2005;Li et al 2006;Mechanic et al 2006;Sak et al 2005;Sanyal et al 2004;Vogel et al 2005;Weiss et al 2005;Ye et al 2006;Zhou et al 2006;Zhu et al 2007) (23 studies) described A33512C, ten articles (Bai et al 2007;Hu et al 2005;Huang et al 2006;Lee et al 2005;Li et al 2006;Sak et al 2006;Shen et al 2005;Weiss et al 2005;Zhou et al 2006;Zhu et al 2007) (11 studies) described C21151T, and 13 articles (Blankenburg et al 2005;Casson et al 2005;De Ruyck et al 2007;Kietthubthew et al 2006;Li et al 2006;Marin et al 2004;Nelson et al 2005;Sak et al 2005;Shen et al 2001;Sugimura et al 2006;Wang et al 2006;Yang et al 2005;Zhu et al 2007) (14 studies) described PAT -/+; 82.1% (23/28) stated that the age and gender status were matched between case and control popul...…”
Section: Study Inclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the 28 eligible articles, 18 articles (Bai et al 2007;Blankenburg et al 2005;Festa et al 2005;Hansen et al 2007;Hirata et al 2007;Hu et al 2005;Huang et al 2006;Kietthubthew et al 2006;Lee et al 2005;Li et al 2006;Mechanic et al 2006;Sak et al 2005;Sanyal et al 2004;Vogel et al 2005;Weiss et al 2005;Ye et al 2006;Zhou et al 2006;Zhu et al 2007) (23 studies) described A33512C, ten articles (Bai et al 2007;Hu et al 2005;Huang et al 2006;Lee et al 2005;Li et al 2006;Sak et al 2006;Shen et al 2005;Weiss et al 2005;Zhou et al 2006;Zhu et al 2007) (11 studies) described C21151T, and 13 articles (Blankenburg et al 2005;Casson et al 2005;De Ruyck et al 2007;Kietthubthew et al 2006;Li et al 2006;Marin et al 2004;Nelson et al 2005;Sak et al 2005;Shen et al 2001;Sugimura et al 2006;Wang et al 2006;Yang et al 2005;Zhu et al 2007) (14 studies) described PAT -/+; 82.1% (23/28) stated that the age and gender status were matched between case and control popul...…”
Section: Study Inclusionmentioning
confidence: 99%
“…Through literature search and selection based on the inclusion criteria, 32 articles (37 studies) were found, and 28 articles (Bai et al 2007;Blankenburg et al 2005;Casson et al 2005;De Ruyck et al 2007;Festa et al 2005;Hansen et al 2007;Hirata et al 2007;Hu et al 2005;Huang et al 2006;Kietthubthew et al 2006;Lee et al 2005;Li et al 2006;Marin et al 2004;Mechanic et al 2006;Nelson et al 2005;Sak et al 2005Sak et al , 2006Sanyal et al 2004;Shen et al 2001Shen et al , 2005Sugimura et al 2006;Vogel et al 2005;Wang et al 2006;Weiss et al 2005;Yang et al 2005;Ye et al 2006;Zhou et al 2006;Zhu et al 2007) (32 studies) met our inclusion criteria, as listed in Table 1. One study of A33512C (Hirata et al 2006) reported an extremely high variant allele frequency, which may result from wrong allele counting or poor genotyping quality, and was finally excluded from our meta-analysis.…”
Section: Study Inclusionmentioning
confidence: 99%
“…There has been increasing evidence that DNA damage plays a critical role in the carcinogenesis of most cancers and DNA En-Jiao Zhang 1 , Zhi-Gang Cui 2 , Zhong-Fei Xu 1 , Wei-Yi Duan 1 , Shao-Hui Huang 1 , Xue-Xin Tan 1 , Zhi-Hua Yin 3 , Chang-Fu Sun 1 , Li Lu 1 * repair genes are considered key genes associated with the onset of cancer (Berwick et al, 2000;Poirier, 2012;Jin et al, 2013). Some repair genes have been reported to be associated with oral cancer (Sugimura et al, 2006;Bau, 2012), including the X-ray repair cross complementing 3 (XRCC3) gene (Flores-Obando et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, several molecular epidemiological studies have investigated the association between the XPA A23G polymorphism and HNSCC risk (11)(12)(13)(14)(15)(16)(17)(18). However, the results remain inconsistent and controversial, partially due to the relatively small sample size of independent studies and sampling effects.…”
Section: Introductionmentioning
confidence: 99%